Perlindungan Hukum Terhadap Jasa Pengiriman Barang Jalur Darat dalam Perspektif Hukum Perdagangan - Ani Yunita; Anisa Ferunika; Nugraheni Indrawati; Fathur Mochammad (Media of Law and Sharia, 2022)
In the service of sending goods through expeditionary routes, there are three routes by land, sea and air. Shipping by land has a very high risk. This research has the aim of first, to find out the legal protection of goods delivery services by land. Second, to find out the responsibility of the goods delivery service company when there is a delay or the goods are damaged on the way of delivery. This type of research uses normative juridical research with statutory approach methods. The results of this study indicate that protection for business actors for the actions of consumers who use goods delivery services that are not in good faith is contained in Law Number 38 of 2009 concerning Post and Law Number 8 of 1999 concerning Consumer Protection. Existing regulations only provide repressive legal protection so that a preventive rule is needed. Goods delivery services by land have a responsibility for goods delivery service companies when there is a delay in delivery, which is to replace costs, as well as compensation for damage to goods based on the Civil Code, the Trade Code and Law No. 8 of 1999 concerning Consumer Protection.